Spanish for beginners - Wilkes, Angela; Shackell, John (Usborne London, 2001)
This title deals with everyday situations in which children may find themselves while abroad. Spanish grammar is clearly explained, and puzzles provide plenty of practice. This title is part of a series providing a thorough grounding in useful, basic language skills.